2015
DOI: 10.1116/1.4919559
|View full text |Cite
|
Sign up to set email alerts
|

Effects of air transient spark discharge and helium plasma jet on water, bacteria, cells, and biomolecules

Abstract: Atmospheric pressure DC-driven self-pulsing transient spark (TS) discharge operated in air and pulse-driven dielectric barrier discharge plasma jet (PJ) operated in helium in contact with water solutions were used for inducing chemical effects in water solutions, and the treatment of bacteria (Escherichia coli), mammalian cells (Vero line normal cells, HeLa line cancerous cells), deoxyribonucleic acid (dsDNA), and protein (bovine serum albumin). Two different methods of water solution supply were used in the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 79 publications
2
51
0
Order By: Relevance
“…This may explain why they are less susceptible to plasma induced depolarization. Previous studies reported that plasma-induced free radicals affect the pH of the media resulting in cell death2223. Because we used PBS as buffering agent we did not observe these changes.…”
Section: Resultsmentioning
confidence: 78%
“…This may explain why they are less susceptible to plasma induced depolarization. Previous studies reported that plasma-induced free radicals affect the pH of the media resulting in cell death2223. Because we used PBS as buffering agent we did not observe these changes.…”
Section: Resultsmentioning
confidence: 78%
“…The distance between the electrodes was 1 cm. Deionized water (DW) or tap water (TW) was supplied via narrow channel in the inclined plane electrode and circulated by a peristaltic pump with a constant flow rate (14 ml/min) to provide repetitive contact of water with the discharge . Transient spark discharge (TS), a self‐pulsing repetitive streamer to spark transition discharge was used to activate water .…”
Section: Methodsmentioning
confidence: 99%
“…They involve sterilization and decontamination of liquids, medical surfaces, implants or skin; influences over cellular processes: wound healing, dermatological diseases, cancer cells targeting; dentistry and related applications and treatment of seeds or vegetal tissues [2]. Cancer treatment is certainly one major topic of research, due to the fact that preliminary results of different groups indicate that selectivity may be achieved under specific plasma treatment conditions [3,4].…”
Section: Introductionmentioning
confidence: 99%